Effectiveness of a Randomized Controlled Hiv-Risk-Reduction Program Field Trial with Students at Ahmadu Bello University Zaria - Abdulmumin, Saad (2010)
Human immunodeficiency virus/ Acquired immune deficiency syndrome (HIV-AIDS) has become the most important infectious disease pandemic of this millennium. Nigeria with over 2.9 million people living with HIV (PLHIV) is at risk of increased burden and transmission of HIV. The country has the second largest burden of HIV infection in the world with young people at the center of the epidemic. The present study aims to evaluate the effectiveness of a peer-led HIV-STI intervention program framed on the Information-Motivation-Behavioral skills model among undergraduate students at Ahmadu Bello University, Zaria in northern Nigeria. We utilized a randomedized controlled field trial design to investigate the impact of an HIV-STI intervention program on participants’ HIV- and STI-related knowledge, sexual risk behaviors, attitudes towards HIV and STI prevention, and disentanglement of stigma. Participants were randomized to either the intervention group or the control group. An 8-hour integrate HIV-STI prevention program comprising of four structured modules was developed and delivered to the intervention group, while the control group received another 8-hour program on career development. Both programs were delivered by trained peers. Two-way repeated measure ANOVA was applied to assess the effectiveness of the intervention. The outcome measures were assessed at baseline, immediately post-intervention, at 3 months and 6 months post-interview. Respondents in the intervention arm showed significant improvements in HIV-related and STI knowledge, sexual risk behaviors and attitudes towards HIV-STI prevention. Conversely, there was no difference in tolerance towards PLHIV assessed using the stigma scale. There were significant main effects for group {F= 155.94, p= < 0.001, η20.401]; time [F = 248.35, p= < 0.001, η2= 0.516} and group x time interaction [F = 162.96, p= <0.001, η2= 0.412] for HIV-related knowledge, sexual risk behaviors, and attitude were also significant. The peer-led HIV-STI intervention program developed was effective in improving knowledge and attitudes towards HIV prevention and reducing sexual risk behaviors among Nigerian university students.